Recent progress in cassava agronomy research in the Philippines - Evangelio, Fernando A.; Ladera, Julieta C. (International Center for Tropical Agriculture, 1998)
During the last three years cassava production in the Philippines did not progress markedly, neither in area nor in volume. In terms of area, there was only an increase of 14,424 ha or 6.4%, while in terms of volume the increase was 112,177 metric tons or 5.7%. One of the reasons for this was the unstable price for chips, especially in 1994/95. Up to the present, cassava cultivation is still concentrated in Mindanao where there are greater opportunities for marketing, particularly trading of dry chips by the San Miguel Corporation and animal feed millers, as well as fresh roots for production of starch. In terms of research, not much data has been generated, since only very few experiments were conducted. Some experiments were terminated, like the one on cropping systems trials in Negros Occidental. In Leyte the fifth cropping cycle of the long-term fertility trial under coconut showed no significant responses to fertilizers, but there were some responses in the sixth year of consecutive cropping. In the erosion control trial, highest soil losses were observed in plots with application of inorganic fertilizers (14-14-14), while the lowest soil losses were observed in plots with vetiver grass barriers or with grass mulch. Root yields were highest with the application of grass mulch or when Crotalaria juncea was intercropped and mulched at 2 months; yields were lowest in plots with lemon grass barriers. The variety x fertilizer trial in Bontoc, southern Leyte, showed a clear varietal response to fertilizers. The variety with a heavier canopy responded more markedly to fertilizer applications. In an intercropping trial in Bohol, even after three cropping cycles, cassava yields were not significantly affected by interplanting of either soybean, mungbean, cowpea, peanut or pole sitao (yard-long bean). However, row spacing significantly affected the yields of cassava and intercrops. In another trial, marked increases in cassava yields were obtained when the plant densify was increased to 15,000-25,000 plants/ha. On the other hand, no significant differences were observed when the age of pruning cassava was varied.